METACOGNITION IN CHILDHOOD: HOW PEDAGOGICAL BIASES OVERLOOK COGNITION IN REGULAR CLASSROOMS - María Elena Ditta Vargas; Juan José Ortiz Valderrama (LÍNEA IMAGINARIA, 2025)
This essay critically examines the invisibilization of metacognition in childhood within mainstream education, attributed to pedagogical biases in conventional models. It underscores the fundamental relevance of this construct for child development, arguing that the predominance of memorization over systematic reflection hinders critical thinking, learning self-regulation, and strategy self-assessment, neglecting individual learning rhythms. Methodologically, a theoretical-critical analysis was conducted through a documentary review of predominant practices, identifying rigid curricular structures and adult-centered authority approaches as key factors. These generate a dissonance between academic content and students’ socio-cultural realities, impeding meaningful knowledge connection with their environment and perpetuating inequities by limiting cognitive agency. Consequently, an urgent transformation of teaching practices is urged, emphasizing continuous professional development to deconstruct such biases and implement flexible strategies that promote intellectual autonomy. It is concluded that integrating metacognition as a core axis for holistic education is imperative, intrinsically aligned with principles of inclusion and critical analysis, seeking to develop children’s abilities not only to learn but to understand how they learn and transfer knowledge meaningfully to their realities.